Short communication. A simple method for trapping Hylobius abietis (L.) alive in northern Spain - Moreira, X.=700 1 Costas, R.; Sampedro, L.; Zas, R.
(En, Es)
ilus., 16 ref.
Keywords: HYLOBIUS ABIETIS; INSECTA; CAPTURA ANIMAL; ATRAYENTES; TREMENTINA; ESPAÑA; HERBIVORIA; INVESTIGACION AGRARIA: SISTEMAS Y RECURSOS FORESTALES